A legalitás és az opportunitás kérdésének dilemmája a pótmagánvád tükrében - Fázsi, László; Fedor, Anett (Debreceni Jogi Műhely, 2012)
The study is focusing on the principles of legality and opportunity regarding the so called substitute private prosecution and sets them against each other. In the study it is revealed that in case analyzing the growing importance of opportunity, under the Hungarian criminal process system – that is based on the principle of legality – there is a logical way to state that the two principles prevail rather together than against each other. The authors take a closer look on the rules of the current criminal process code, arising from the principle of opportunity and suggest a possible solution on the dogmatic problem how these two principles can exist at the same time in the substitute private prosecution.Based on rationalism, on the recommendation No. Rec(2000)19 of the Council of Europe and so that no conflicts arise from the provisions foreseen in the Framework Decision No. 2001/220/IB of the European Council, the study makes a suggestion to allow the victim to act as a substitute private prosecutor in case of authorities partially deny the investigation. However the authors’ suggestion is just the opposite (i.e. restriction) in case of authorities partially deny indictment. According to their suggestion the above mentioned allowance shall based always on reasonable and respectable circumtances and it shall be declared by the victim why the process at the court has to take place even if authorities were not of this opinion.When the authors are analyzing the problems caused by the principle of opportunity and legality, and when they make suggestions that the rules regarding the substitute private prosecution shall be modified, they try to draw attention on the importance of this process as a significant right of victims regarding access to justice. The authors are on the opinion that the legislator shall pay not just a marginal attention on the problem when the victims are entitled to act as an substitute private prosecutor.